Investigação do mecanismo da atividade antifúngica de monoterpenos frente a cepas de Trichophyton rubrum. - Pereira, Fillipe de Oliveira (2012)
Trichophyton rubrum is the main responsible microorganism of chronic cases of dermatophytosis on nails, feet, hands, torso, neck and scalp, with high rates of resistance to antifungal agents. The clinical and epidemiological importance concerned dermatophytosis encourage studies for searching of new antifungal agents. In this context, attention has been drawn to the products from aromatic plants, especially essential oils and their components. The monoterpenes stands out due to widespread recognition of its antimicrobial activity. Therefore, it was investigated the antifungal activity of the monoterpenes citronellal, geraniol and citronellol against 14 strains of T. rubrum. For this, it was determined the minimum inhibitory concentration (MIC) of each drug, as well as their effects on mycelial growth (dry weight), the viability (logCFU/mL), conidial germination and morphogenesis. The action of the drugs on the fungal cell wall (test with sorbitol) and on the fungal cell membrane (release of cellular material, complex with ergosterol and ergosterol synthesis) were also investigated. Moreover, it was analyzed the interference on the infectivity of T. rubrum (in vitro nail infection). Among the tested monoterpenes, geraniol and citronellol were the most potent, since they showed lower MIC values. Assays were performed with geraniol (MIC = 32 μg/mL and MICx2 = 64 μg/mL) and citronellol (MIC = 128 μg/mL and MICx2 = 256 μg/mL), they significantly inhibited the mycelial growth and conidial germination. The monoterpenes showed fungicidal effect and caused caused abnormalities in morphogenesis showing large, short and twisted hyphal in the strains ATCC1683 and LM422. With sorbitol, the MIC values of these monoterpenes increased against the strain ATCC1683, suggesting action on the fungal cell wall. The results of the assays on the cell membrane showed that geraniol and citronellol released intracellular material, formed complexes with the ergosterol and decreased content of ergosterol. Therefore, the results suggest that that geraniol and citronellol act on the membrane of T. rubrum by a mechanism that appears to involve a complex with ergosterol and inhibition its biosynthesis, indirectly affecting the cell wall and causing cell lysis. Moreover, geraniol and citronellol at MIC and MICx2 also prevented infection of T. rubrum on nail fragments. Thus, the monoterpenes geraniol and citronellol are presented as promising antifungal agents, with potential applicability in the treatment of dermatophytosis, especially against the agent T. rubrum.